التسرب المدرسي وعلاقته بالعنف اللفظي - حمدان, سليم; عامر, سمية; بوعافية, منال (University of Eloued جامعة الوادي, 2020)
تواجه الجزائر عدة مشكلات، ومتغيرات اجتماعية واقتصادية مختلفة، أهمها ظاهرة التسرب المدرسي، التي تشكل هدرا تربويا ضخما، وهي من المشاكل التي تعاني منها المدارس الجزائرية فهي تعد معضلة من المعضلات التي تواجه المجتمع على وجه العموم، والنظام التربوي على وجه الخصوص، والتي تؤثر سلبا على الفرد والمجتمع خاصة مع تفشي هذه الظاهرة في الوسط المدرسي، الذي يعدّ البيئة الأساسية للتنشئة الصالحة للتلاميذ في مختلف المراحل التعليمية. إن مسألة العنف اللفظي - التي هي أحد أهم أسباب هذه الظاهرة- تظهر بسبب ظروف معينة وتختلف من زمن إلى زمن ومن مجتمع إلى آخر، من أجل ذلك سنحاول في هذه المداخلة عرض ملامح العنف اللفظي وعلاقته بالتسرب المدرسي في ظل المتغيرات الاجتماعية والاقتصادية والنفسية، من خلال التعرف على الدوافع والأسباب المختلفة والآثار المترتبة عن ذلك، ثم محاولة تقديم مقترحات للحد من هذه الظاهرة، أو حتى القضاء عليها، لذلك ارتأينا أن تكون مداخلتنا بعنوان: ظاهرة التسرب المدرسي وعلاقته بالعنف اللفظي وانطلقت المداخلة من إشكال رئيس مؤداه: *هل من الممكن أن يكون العنف اللفظي من الأسباب الرئيسة في ظاهرة التسرب المدرسي؟ Abstract : Algeria faces several problems, and various social and economic variables, the most important of which is the phenomenon of school dropout, which constitutes a huge educational waste, and it is one of the problems that Algerian schools suffer from as it is one of the dilemmas facing society in general, and the educational system in particular, which negatively affects On the individual and society, especially with the spread of this phenomenon in the school environment, which is considered the basic environment for suitable education for students at various educational levels. The issue of verbal violence - which is one of the most important causes of this phenomenon - appears due to specific circumstances and varies from time to time and from one society to another, for this we will try in this intervention to show the features of verbal violence and its relationship to school dropout in light of social, economic and psychological variables, through Identify the motives, the various causes and the implications of that, then try to make proposals to reduce this phenomenon, or even eliminate it, so we considered our intervention to be entitled: The phenomenon of school dropout and its relationship to verbal violence The intervention was based on a problem that a president performed: * Is it possible that verbal violence is one of the main causes of the school dropout phenomenon?
School dropout and its relationship to verbal violence
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: التسرب المدرسي، العنف اللفظي، المعلم، المتعلم، الأسرة; School dropout, verbal violence, educated